The Pacifying Power of Wages in the Domestic Work Domain - Vuyo Gama (The Thinker)
Historically, scholarship on domestic work in Africa has characterised the sector as oppressive. As an integral part of the oppressive nature of the domestic work domain, this article investigates the contradictions associated with the admirable act of employers paying their domestic workers more than recommended minimum wage in Eswatini. Previously known as Swaziland, Eswatini is a small, interlocked country between South Africa and Mozambique. The country’s recommended minimum wage for domestic workers is E 1,246.00 (USD 73.20) per month. Interviews were conducted among ten live-in domestic workers from Tubungu, Eswatini, who earn E 3,500 (USD 205.63) or more per month. This article relies on in-depth interviews to establish the dynamics at work in this act of constructive remuneration. The study’s findings challenge the assumption that higher paid wages in the domestic sector are always a well-intentioned and successful achievement of one aspect of the ‘decent work’ agenda. Findings show that higher wages subtly increase domestic workers’ tolerance of employers’ disregard of other working conditions. This is at the expense of the domestic workers’ well-being and pacifiers their ability to challenge their employers about other working conditions as their entitlement. The study shows how both liberating and oppressive experiences, not just oppression, coexist within the domestic work landscape in Eswatini. This points to an interesting ambiguity in the domestic work field. Finally, the study shows how these contradictory oppressive and liberatory experiences both inform and sustain domestic work in the country. This is in a context where women are part of a labour market with high unemployment, with domestic work being a convenient source of employment for less-skilled labour.